Non-ICANS neurotoxicities CD19-directed CAR T-cell therapy and the emergence of movement and neurocognitive treatment-emergent adverse events: a case report - Schroeder, Torsten; Chitadze, Guranda; Dargvainiene, Justina; Martens, Tjark; Gebauer, Niklas; Frimmel, Julia; Brüggemann, Monika; Valerius, Thomas; Schub, Natalie; Baldus, Claudia D.; Pott, Christiane; Leypoldt, Frank; et al. (Frontiers in Immunology, 2026)
We report a 63-year-old male patient with diffuse large B-cell lymphoma (DLBCL) who developed delayed-onset neurotoxicity on day +22 following CD19-directed CAR T-cell therapy with axicabtagene ciloleucel (axi-cel), after an initial episode of CRS and ICANS. The underlying disease had relapsed with secondary central nervous system (CNS) involvement, highlighting a high-risk setting for neurotoxicity. Unlike classical ICANS, the syndrome featured progressive gait ataxia and hypokinetic movement disturbances—clinical hallmarks of so-called movement and neurocognitive treatment-emergent adverse events (MNTs), a syndrome often referred to as parkinsonism due to characteristic features such as bradykinesia, rigidity, tremor, and cognitive slowing. To date, such MNTs have only been reported in patients receiving BCMA-targeted CAR T-cell products, primarily for multiple myeloma. Our report is, to the best of our knowledge, the first documented case of an MNT-like syndrome following CD19-directed CAR T-cell therapy. The patient’s symptoms evolved subacutely, in the absence of radiographic progression, infection, or lymphoma relapse. Immunophenotyping revealed activated effector-memory CD8+ T cells (HLA-DR+/CD38+/CD28-/PD1+) in peripheral blood, and predominantly CAR T cells in cerebrospinal fluid. Neurofilament light chain (NfL) levels rose significantly in serum and CSF, indicating neuroaxonal injury. Steroid therapy led to partial clinical improvement. Follow-up neuropsychological testing revealed persistent deficits in attention and processing speed. This case broadens the known neurotoxicity spectrum of CAR T-cell therapies and underscores the need for heightened clinical vigilance and refined diagnostic criteria beyond ICANS, even in CD19-targeted settings.